Snapshot of health-related behaviours in adults living with disabilities 1 year into the COVID-19 pandemic: a cross-sectional survey study - Syeda F Hussain; Nikki Heinze; Claire L Castle; Lauren R Godier-McBard; Theofilos Kempapidis; Renata S M Gomes (BMJ Open)
Objectives This survey aimed to assess the status of a range of health-related behaviours 1 year after the coronavirus outbreak was declared a pandemic in adults living with disabilities comparative with those with no disabilities.Design This cross-sectional study reports findings from an online survey conducted in March 2021. Mann-Whitney U and Χ2 tests were used to compare a range of health behaviours including time spent self-isolating, smoking, alcohol consumption, exercise frequency and diet in adults with and without disabilities.Setting A convenience sample of UK adults was recruited through the researchers’ personal and professional networks including UK-based sight loss sector charities, social media platforms and professional forums.Participants A total of 123 UK participants completed the survey.Outcome measures COVID-19 diagnosis, time spent self-isolating, alcohol consumption frequency, exercise frequency, change in smoking habit and eating habits.Results No significant differences were found in alcohol consumption, smoking, water intake, breakfast, or fruit and vegetable intake. There were statistically significant differences in the time spent self-isolating (U=2061, p=0.001), exercise frequency (U=1171.5, p=0.005) and the amount of food eaten (χ2 (2)=9.60, p=0.008, Cramer’s V=0.281). Although the majority in both groups reported exercising three to four times per week and eating what they should, those with disabilities were more likely to eat less than they should, not exercise at all and to have been self-isolating for over 6 months than participants with no disabilities.Conclusions The data in this study present some key differences between the two groups, with those living with disabilities being more likely to report that they had been self-isolating for prolonged periods of time, not exercising at all, and not eating as much as they should . This raises concerns for the health and well-being of individuals with disabilities.